Influence of environmental drivers on the plankton distribution on the inner shelf off Ubatuba, southeastern Brazil - Penninck, Silvana Simone Batista (2022)
With the general objective of evaluating the spatiotemporal distribution of plankton under different environmental conditions, governed by physical processes, on the inner shelf off Ubatuba (SP), Brazil, considering more detailed vertical and spatial resolutions, three independent studies were carried out. These studies are presented throughout this thesis in the form of scientific articles, in chapters II to IV. In chapter II, the occurrence of thin layers of phytoplankton and their temporal evolution were investigated over two days of observations in February/2019. Chapter III analyzed seasonal (winter/summer) and short-term variation (hours) in the plankton abundance and distribution and their relationship with hydrodynamic conditions, based on observations carried out in July/2018 and January/2019. In chapter IV the influence of environmental conditions on the abundance and vertical and horizontal distributions of the Synechococcus, Prochlorococcus, picoeukaryotes, and nanoeukaryotes populations was evaluated, comparing different scenarios obtained in December/2018 and January/2019. Overall, the data collection relied on field observation techniques at fixed and spatial stations, continuous high-resolution profilings with optical and acoustic sensors, in addition to discrete sample collection for analysis in laboratory. The abundance of the main plankton groups, from autotrophic microorganisms to mesozooplankton, was estimated using an in situ imaging system and flow cytometry (pico-nanoplankton). The general results suggest that the wind is the primary forcing of the variability in the plankton abundance and vertical and horizontal distribution in the coastal zone of Ubatuba, driving submesoscale phenomena related to the intrusion and retreat of the South Atlantic Central Water along the inner shelf and vertical mixing processes in events of change in the wind pattern, especially when associated with frontal systems. The present thesis makes an original contribution to the knowledge about the influence of physical processes on plankton distribution in high spatio-temporal resolution in a subtropical coastal ecosystem.